2012
DOI: 10.5415/apallergy.2012.2.1.35
|View full text |Cite
|
Sign up to set email alerts
|

IgE cross-reactivity between house dust mite allergens and Ascaris lumbricoides antigens

Abstract: BackgroundCommon antigens between intestinal parasites and environmental allergens may play a role in the modulation of allergic immune responses. There is a growing interest in investigating cross-reactivity between common helminths and dust mites affecting humans, particularly in the tropics.ObjectiveThis study examined the cross-reactivity between the human roundworm Ascaris lumbricoides (Al) and three house dust mite (HDM) species.MethodsSpecific serum IgE levels to HDM species Blomia tropicalis (Bt), Derm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 30 publications
(44 reference statements)
2
26
0
Order By: Relevance
“…It clearly indicates that many of the children with geohelminthiasis were more prone to be allergic to inhalants than seafood. According to Barreto et al (2006), Fallon and Mangan (2007) and Lee et al (2013), this may suggest that intestinal parasitic infection may play a role in the development of atopy notably, respiratory allergies Alcântara-Neves et al, 2010;Cauyan et al, 2012;Beyers et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It clearly indicates that many of the children with geohelminthiasis were more prone to be allergic to inhalants than seafood. According to Barreto et al (2006), Fallon and Mangan (2007) and Lee et al (2013), this may suggest that intestinal parasitic infection may play a role in the development of atopy notably, respiratory allergies Alcântara-Neves et al, 2010;Cauyan et al, 2012;Beyers et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Data regarding the children's demographic profile and allergic diseases were collected from the parent/guardian by employing the International Study of Asthma and Allergies in Childhood Phase I questionnaire as patterned from previous studies of Dubois, Kerkhof, Monchy, Postma, and Schouten (2003), Cauyan et al (2012), Alcântara-Neves, Badaró, Barreto, dos Santos, and Pontes-de-Carvalho (2010) and Amarasekera et al (2012). It was slightly modified with the addition of core questionnaire for food allergy, translated to Filipino and subjected to face validation from their advisers and a panel of experts such as pediatrician, immunologist, linguist and psychologist.…”
Section: Blood Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…[116][117][118][119][120][121][122][123][124][125][126][127][128] We have demonstrated that helminth infection can be associated with increased IgE responses to many different allergens, especially those structurally related to parasite antigens. 116 Individuals infected with filarial parasites were shown to have higher levels of IgE against HDM and cockroach extracts (that have several major allergens with homologues in filarial parasites) but not against timothy grass extract, an allergen extract with just a few minor allergen homologues in helminths.…”
Section: -89mentioning
confidence: 99%